Optimum Design of Cone Type Friction Clutch based on Fuzzy Comprehensive Evaluation - Yang Yongqiang; Li Xiaoying; Cao Botao; Zhang Chunxia; Zhang Man (Jixie chuandong)
Based on the dynamics research,an optimum mathematical model of cone type friction clutch is established with the working space for the optimization objective.Aiming at the fuzzy factor analysis of some important design parameters,the fuzzy comprehensive evaluation method is used to optimize this clutch.It is shown by calculation that the working space can be obviously decreased by optimization.Therefore,this optimization method provides the theoretical foundation to research the performance of cone friction clutch.